Separation enhancement of palm kernel by its specific gravity and flow rate of clay water bath - Jimy, Ronald Atorm (2012)
In palm oil industry,there are two major product obtained from palm oil fruit the palm oil and the palm oil kernel. Palm oil kernel is obtained from the Fresh Fruit Bunches after the pressing of the fruits.The leftover from the press was a mixture of fiber and nuts.After separating the fiber and nuts, these nuts were then cracked using ripple mill and a mixture of shell and kernel were produced.There are two ways to separate this two component,using hydrocyclone and clay water bath.This experiment will investigate the best ratio of water and kaolin to achieve the best separation of the shell and kernel.The parameters investigated were the Specific Gravity value of this kaolin mixture and the rotation speed of the cyclone.The clay bath principle works on the specific gravity of kernel of 1.07 and the shell of 1.17.The claybath will then be introduced with kaolin mixture using various value of Specific Gravity. The values investigated were 1.06, 1.08, 1.10, 1.12, 1.14, 1.16, 1.18 and 1.20.The kernel will started to float at Specific Gravity 1.08 and shell will start to float at Specific Gravity of 1.18.By drawing the graph of Separation Percentage versus Specific Gravity,the best Specific Gravity will then be able to be determined.After achieving the best separation Specific Gravity,flow rate of clay bath will then be tested.Flow rate of clay bath can be controlled using the pump.Various flow rate will be tested to see which produces the best separation ratio of kernel and shell.As a conclusion,the best specific gravity for clay bath was 1.16 and the flow rate that produces optimum separation was 70m³/s.